Methods of finding individual characteristics of aircraft by using the data of board systems recording the flight information - Ищенко, С. А. (Proceedings of National Aviation University (archive), 1998)
Considered is the method of estimation of characteristics of a given aircraft by using the data of expenditure characteristics registered by the board systems of accumulation of flight information. Using the aircraft EL-86 as a model we show that there is a possibility to determine the causes of appearance of individual characteristics and to take them into account in the process of flight operations